Repeated word production is inconsistent in both aphasia and apraxia of speech. Issue 4 (3rd April 2021) - Haley, Katarina L.; Cunningham, Kevin T.; Jacks, Adam; Richardson, Jessica D.; Harmon, Tyson; Turkeltaub, Peter E.
ABSTRACT: Purpose : There is persistent uncertainty about whether sound error consistency is a valid criterion for differentiating between apraxia of speech (AOS) and aphasia with phonemic paraphasia. The purpose of this study was to determine whether speakers with a profile of aphasia and AOS differ in error consistency from speakers with aphasia who do not have AOS. By accounting for differences in overall severity and using a sample size well over three times that of the largest study on the topic to date, our ambition was to resolve the existing controversy. Method : We analyzed speech samples from 171 speakers with aphasia and completed error consistency analysis for 137 of them. The experimental task was to repeat four multisyllabic words five times successively. Phonetic transcriptions were coded for four consistency indices (two at the sound-level and two at the word-level). We then used quantitative metrics to assign participants to four diagnostic groups (one aphasia plus AOS group, one aphasia only group, and two groups with intermediate speech profiles). Potential consistency differences were examined with ANCOVA, with error frequency as a continuous covariate. Results : Error frequency was a strong predictor for three of the four consistency metrics. The magnitude of consistency for participants with AOS was either similar or lower compared to that of participants with aphasia only. Despite excellent transcription reliability and moderate to excellent coding reliability, three of the four consistency indices showed limited measurement reliability. Discussion : People with AOS and people with aphasia often produce inconsistent variants of errors when they are asked to repeat challenging words several times sequentially. The finding that error consistency is similar or lower in aphasia with AOS than in aphasia without AOS is incompatible with recommendations that high error consistency be used as a diagnostic criterion for AOS. At the same time, group differences in the opposite direction are not sufficiently systematic to warrant use for differential diagnosis between aphasia with AOS and aphasia with phonemic paraphasia. Greater attention should be given to error propagation when estimating reliability of derived measurements.